USING SCHOOL.DUOLINGO.COM AS AN ALTERNATIVE E-LEARNING AT SENIOR HIGH SCHOOL FOR TEACHING AND LEARNING ENGLISH ONLINE - Arima Mulya; Refnaldi Refnaldi (Universitas Negeri Padang, 2016)
The current technological and communication development affects almost all the aspects of human life, and one of them is in education. In English teaching, technological development has a positive impact; it is about teaching English through E-learning. In E-learning, there are a lot of media that can be used by the teacher and the students to support learning English. One of them is through online learning (teaching methods via internet). In online learning, using website can help the teacher and the students to teach and learn English through E-learning. School.duolingo.com is one of the websites that can be used by the teacher and the students as a media to teach and learn English. This website has interesting features that can increase students’ interest and motivate them to learn English. The teacher can also check the progress of the students in school.duolingo.com. Through this paper the author hopes that all teachers to be more creative in using media in order to increase interest and motivation of the students to learn English.